Existence and Nonuniqueness of Weak Solutions for a Degenerate Diffusion Equation (Journal of Partial Differential Equations, 2005)
In this paper, we prove the existence and nonuniqueness of the weak solutions of the initial and boundary value problem for a nonlinear degenerate parabolic equation not in divergence form. Localization property of weak solutions will be also discussed.
Keywords: Divergence form; degenerate parabolic equation; existence; non-uniqueness; localization